Investigating improvements in premature death in two rural, majority-minority counties in the south. (August 2020) - Lyn, Rodney; Heath, Erica; Torres, Andrea; Andrews, Christine
Abstract: This exploratory study investigates counties in the southeast United States with mortality outcomes that were better than might be expected given their sociodemographic profiles (i.e., positive deviance). This study seeks to understand the community characteristics with the potential to moderate the negative health outcomes typically associated with social, geographic, or economic disadvantages. This article describes the process used to identify positive deviants and reports on the findings from key informant interviews in positive deviant counties to identify community factors or practices that might contribute to positive deviance in the observed outcomes. County Health Rankings and Roadmaps 2015 data and mortality trends were examined to identify positive deviant counties. The inclusion criteria were median household incomes in the lowest tertile of their state, ≥ 33% African American, and premature mortality rankings (as measured by Years of Potential Life Lost–YPLL) in the top quartile within their state. After benchmarking county rates against national figures and retaining counties with significant improvement trends, two counties emerged as positive deviants, Dooly County, Georgia and Washington County, North Carolina. Key informant interviews (n = 11) were conducted with community stakeholders in the study counties to better understand the community characteristics that could lead to the observed outcomes. Interview data were analyzed using qualitative methods. Key informant interviews revealed three emergent themes: 1. accessibility and availability of healthcare, 2. the provision of a robust EMS system, and 3. coordination of county-funded services targeting vulnerable populations. The positive deviance framework provides a foundation for the identification of community factors or practices with the potential to create a 'culture of health' in communities at the greatest risk for adverse health outcomes. Our findings suggest that healthcare supported by the coordination of non-emergency transportation and health and social services across numerous stakeholders may have contributed to observed outcomes in the study counties. Highlights: This study investigated premature mortality trends in counties in the southeast United States. Two counties out of the 131 counties examined met the criteria for inclusion. Community stakeholders (n=11) were identified and interviewed as part of a site visit to the study counties. For premature death in the County Health Rankings, Dooly County ranked 20th in Georgia in 2015. For premature death in the County Health Rankings, Washington County ranked 23rd in North Carolina in 2015.